Analisis Pengaruh Perputaran Modal Kerja Dan Keputusan Investasi Terhadap Profitabilitas (Studi Pada Perusahaan Berbasis Internet Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024) - Septiani Juniarti; Yennida Parmariza; Vidya Ayu Diporini (Bajang Institute, 2026)
This study aims to analyze the effect of working capital turnover and investment decisions on the profitability of internet-based companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach with a causal research design. The population consisted of six internet-based companies listed on the Indonesia Stock Exchange. A saturated sampling technique was applied, in which the entire population was used as the research sample. Secondary data were obtained from the companies' annual financial statements and analyzed using panel data regression with the Fixed Effect Model (FEM). The results indicate that working capital turnover has a positive and significant effect on profitability, as measured by Net Profit Margin, while investment decisions, proxied by the Price Earnings Ratio, have no significant effect on profitability. Simultaneously, the two independent variables were unable to explain variations in profitability significantly, suggesting that other factors outside the proposed model play a more dominant role in influencing the profitability of internet-based companies. These findings highlight that efficient working capital management is a key factor in enhancing corporate profitability amid the dynamic digital industry and may serve as a valuable consideration for management in formulating more effective financial policies